(3TQM bhGYO GdCMcGes - (3GdORahdj, GdcGXej, GdCfUGQj, GdJSJQj, MSf Hf CSO Gddg Hf ESeGYjd, J (B1298(3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj GTJb fhQ GdhLhO ef XdeI GdYOe(B... (3EeG HYO aEfg cGf jNJd aj NGWQj (B... (3Cf CTQM bhGYO GdYdGeI(B... (3aTQYJ eYJeOG Ydi Gdedc(B... (3cJGH GdeYGedGJ(B...s
(3BNQgG (B:s
(3hXghQ GLJeGY Gdehbha Ydjge Ydi Pdc ajeG Od Ydi Jhdjge (B... (3Hd eY GdehGab efgG ddbhGYO NGUIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B184s
(3eYLe GdeDdajf(B: (3L(B1(3, U(B539s
(3GdPQjYI HQbe(B: 1559s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis